HA N193D substitution in the HPAI H5N1 virus alters receptor binding affinity and enhances virulence in mammalian hosts - Seung-Gyu Jang; Young-Il Kim; Mark Anthony B. Casel; Jeong Ho Choi; Ju Ryeon Gil; Rare Rollon; Eun-Ha Kim; Se-Mi Kim; Ho Young Ji; Dong Bin Park; Jungwon Hwang; Jae-Woo Ahn; et al. (Emerging Microbes and Infections)
During the 2021/2022 winter season, we isolated highly pathogenic avian influenza (HPAI) H5N1 viruses harbouring an amino acid substitution from Asparagine(N) to Aspartic acid (D) at residue 193 of the hemagglutinin (HA) receptor binding domain (RBD) from migratory birds in South Korea. Herein, we investigated the characteristics of the N193D HA-RBD substitution in the A/CommonTeal/Korea/W811/2021[CT/W811] virus by using recombinant viruses engineered via reverse genetics (RG). A receptor affinity assay revealed that the N193D HA-RBD substitution in CT/W811 increases α2,6 sialic acid receptor binding affinity. The rCT/W811-HA193N virus caused rapid lethality with high virus titres in chickens compared with the rCT/W811-HA193D virus, while the rCT/W811-HA193D virus exhibited enhanced virulence in mammalian hosts with multiple tissue tropism. Surprisingly, a ferret-to-ferret transmission assay revealed that rCT/W811-HA193D virus replicates well in the respiratory tract, at a rate about 10 times higher than that of rCT/W811-HA193N, and all rCT/W811-HA193D direct contact ferrets were seroconverted at 10 days post-contact. Further, competition transmission assay of the two viruses revealed that rCT/W811-HA193D has enhanced growth kinetics compared with the rCT/W811-HA193N, eventually becoming the dominant strain in nasal turbinates. Further, rCT/W811-HA193D exhibits high infectivity in primary human bronchial epithelial (HBE) cells, suggesting the potential for human infection. Taken together, the HA-193D containing HPAI H5N1 virus from migratory birds showed enhanced virulence in mammalian hosts, but not in avian hosts, with multi-organ replication and ferret-to-ferret transmission. Thus, this suggests that HA-193D change increases the probability of HPAI H5N1 infection and transmission in humans.